A general formulation for solid solution hardening effect in multicomponent alloys. (15th January 2017) - Toda-Caraballo, I.
Abstract: This paper presents a general formulation for the effect of the solid solution hardening (SSH) in multicomponent alloys. It bridges the existing approaches analyzing this hardening effect between binary alloys and highly concentrated multicomponent systems. The model is validated with a comprehensive dataset of measured critical resolved shear stress, hardness and yield strength of binary and multicomponent systems from the literature. Graphical Abstract: